Dystocia due to torsion in non-descript buffalo - KUMAR, H; MEHROTRA, S; SARATH, T; SUGUNA, K; PATRA, M K; MUTHDKUMAR, K (The Indian Journal of Animal Reproduction, 2007)
A case of dystocia due to right side post cervical uterine torsion of more than 270° in a non-descript parous buffalo and its successful management using modified schaffcr’s method is reported.